(untitled) (Iranian Journal of Kidney Diseases, 2009)
Introduction. Acute kidney failure (AKF) is a common clinical problem in neonatal intensive care units and is usually associated with a contributing condition such as sepsis, asphyxia, and heart failure. The aim of this study was to determine the types, frequency of associated contributing conditions, and short-term outcome of neonatal AKF. Materials and Methods. Medical records of neonates with a diagnosis of AKF from March 2003 to September 2006 were studied in a tertiary care children’s hospital in Tabriz, Iran. Results. Of 6042 hospitalized neonates, 151 with documented AKF (100 boys and 51 girls) were reviewed in the study. Ninety-one patients (60.3%) had been referred from other cities. Fifty-seven patients (37.7%) developed AKF following a surgery. Causes of AKF were intrinsic kidney failure in 52.3%, prerenal in 42.4%, and postrenal in 5.3%. Oliguria was observed in 72.2% of the patients. Perinatal asphyxia was present in 29.8% of the neonates, sepsis in 28.5%, respiratory distress syndrome in 25.2%, dehydration in 24.2%, and heart failure in 21.2%. Most patients (85.4%) had more than 1 associated contributing condition. Mortality rate was 20.5%. Most patients (76.2%) were discharged with normal kidney function and 3.3% with diminished kidney function. Initial admission to NICU, female sex, septicemia, and the need for mechanical ventilation were associated with a higher mortality rate. Conclusions. The frequency of associated contributing conditions and short-term outcome of neonatal AKF in our institution is comparable with other studies; however, intrinsic kidney failure comprises the most common form of AKF in our patients.